CORRECTION OF SEQUELAE FOLLOWING ORBITO-ZYGOMATIC FRACTURES - Victor Vlad Costan; Cristian Ilie Drochioi; Andrei Nicolau; Daniela Sulea; Andrada Doscas; Marius Dabija (Romanian Society of Oral Rehabilitation, 2019)
Aim: The purpose of this article is to share our experience regarding the late correction of orbito-zygomatic fracture sequelae. Material and Methods: We performed a review including 14 patients that underwent corrective surgery for functional or cosmetic impairment resulted from malunioned orbito-zygomatic fractures, between January 2013 and December 2017. Results: The posttraumatic sequelae were following two orbital blow-out fractures, four terapodal zygomatic bone fractures and eight comminuted orbito-zygomatic fractures. Most patients presented for diplopia and facial asymmetry. The procedures used for the correction of the various defects were titanium mesh reconstruction of the orbital floor, of the orbital contour and zygomatic bone, osteotomy and repositioning of the zygomatic bone, fat transfer and silicone implant placement for facial asymmetry correction, ectropion correction. The postoperative complications encountered were periorbital edema and ecchymoses. Overall, favourable outcomes were achieved postoperative with functional rehabilitation, including the disappearance of diplopia within one month in all involved cases, and the restoration of facial symmetry. Conclusion: Form and function can be accurately restored by performing procedures suitable to the individual defect, targeting the recontouring of the bone frame and the rearrangement of the overlying soft tissues, considering the degree of involvement.